Mental distress among young people in inner cities: the Resilience, Ethnicity and AdolesCent Mental Health (REACH) study. Issue 6 (8th February 2021) - Knowles, Gemma; Gayer-Anderson, Charlotte; Beards, Stephanie; Blakey, Rachel; Davis, Samantha; Lowis, Katie; Stanyon, Daniel; Ofori, Aisha; Turner, Alice; Working Group, Schools; Pinfold, Vanessa; Bakolis, Ioannis; et al.
Abstract : Background: Recent estimates suggest around 14% of 11–16 years in England have a mental health problem. However, we know very little about the extent and nature of mental health problems among diverse groups in densely populated inner cities, where contexts and experiences may differ from the national average. Aims: To estimate the extent and nature of mental health problems in inner city London, overall and by social group, using data from our school-based accelerated cohort study of adolescent mental health, Resilience, Ethnicity and AdolesCent Mental Health. Methods: Self-report data on mental health (general mental health, depression, anxiety, self-harm) were analysed (n, 4353; 11–14 years, 85% minority ethnic groups). Mixed models were used to estimate weighted prevalences and adjusted risks of each type of problem, overall and by gender, cohort, ethnic group and free school meals (FSM) status. Results: The weighted prevalence of mental health problems was 18.6% (95% CI 16.4% to 20.8%). Each type of mental health problem was more common among girls compared with boys (adjusted risk ratios: mental health problems, 1.33, 95% CI 1.18 to 1.48; depression, 1.52, 1.30 to 1.73; anxiety, 2.09, 1.58 to 2.59, self-harm, 1.40, 1.06 to 1.75). Gender differences were more pronounced in older cohorts compared with the youngest. Mental health problems (1.28, 1.05 to 1.51) and self-harm (1.29, 1.02 to 1.56)—but not depression or anxiety—were more common among those receiving (vs not receiving) FSM. There were many similarities, with some variations, by ethnic group. Conclusions: Adolescent mental health problems and self-harm are common in inner city London. Gender differences in mental health problems may emerge during early adolescence.